Al Sindi bin Shahik and his affection in arab Islamic country in the reign of first Abbaas n reign 132-232 imm . 749-847 christ ynia - أسعد عبد الحميد طه مها (Al-Adab Journal, 2018)
the circumastances of Islamic Arab country affected to the appreeance of many characters in the reign of Abbasynian khilapha .some of them affected honestly in the building of Abbasynian country and whom affected in destroying and separating the segrigarion and scatter and some who induljed in seditions and disturbances in order to make it destroyed . and the third kind who was confused because of his fearness of the order of the strong ruler , colouring by the circumstances and the series of events in the earth . so who is writing the history pages not populations and heros only , but the laggard and colourful people write it sometimes . so I have chosen the subject of the research as ( al – sindi bim shahik ) who had represented the final case in confusing and colouring and effected by the events in the first abbysinian term